О динамике короткопериодических комет - Емельяненко, В.В. (Кинематика и физика небесных тел, 1987)
Численно изучена эволюция орбит наблюдавшихся короткопериодических комет на промежутках времени до 50 000 лет. Рассмотрены особенности их либрационного и стохастического движения. Выделены кометы, не имеющие вблизи современной эпохи тесных сближений с Юпитером. The evolution of the observed short-period comets is studied numerically on the time intervals reaching 50 000 years. The peculiarities of comet’s libratory and stochastic motion are considered. The comets which do not make close approaches to Jupiter near the contemporary epoch are indicated.